THE ROLE OF USAID (U.S. AGENCY FOR INTERNATIONAL DEVELOPMENT) IN ENCOURAGING DEMOCRACY IN INDONESIA - Irani Siti Nurkholidah (2012)
This undergraduate thesis try to explore the role of USAID (U.S. Agency for International Development) especially in encouraging democracy in Indonesia. The dilemma of foreign aid become one of background in this paper, where developing country needed, but others said that it is domination from developed country as the donors. USAID come to Indonesia, because USAID consider Indonesia still need assistance. With the limitation aspect only in democracy, the writer use concept of foreign aid and co